Kelayakan Usahatani Jagung Pipil pada Perkebunan Kelapa Sawit di Desa Negeri Bumi Putra Kecamatan Umpu Semenguk Kabupaten Way Kanan - Lestari, Marta Duwi; Zebua, Damara Dinda Nirmalasari (Universitas Galuh, 2026)
Corn farming in immature oil palm plantations has become one of the alternative land-use strategies in Way Kanan Regency, particularly in Negeri Bumi Putra Village, Umpu Semenguk District. Farmers in this area utilize oil palm plantation land by intercropping corn to increase their income. This study aims to: (1) determine the production costs, revenue, and income of corn farming; and (2) analyze the feasibility of corn farming. The research used a descriptive quantitative approach with 17 corn farmers as respondents. Data were collected through interviews and direct field observations. The collected data were analyzed using Microsoft Excel. The results showed that (1) the total average production cost reached IDR 16.340.341,91 per hectare per planting season, with the largest component coming from labor costs amounting to IDR 8,688,665.44 per hectare. The total revenue obtained by farmers reached IDR 30.493.673,18 per hectare, resulting in a net income of IDR 14.153.331,27 per hectare; and (2) the R/C ratio value was 1.90 >1, indicating that every one rupiah of cost incurred would generate a return of 1.90 rupiah. Therefore, shelled corn farming in oil palm plantations in Negeri Bumi Putra Village is feasible and profitable to cultivate.